Coercivity for One-dimensional Cell Vertex Approximations - Morton, K (Unspecified, 1996)
Previous error analysis for the cell vertex scheme has been limited to situations where the cell residuals can be set to zero. However, in practical use for compressible flow computations it is necessary to extend the method by the use of distribution matrices and the careful addition of artificial viscosity terms. In this paper we make a start on the error analysis that is required for this more general method. The chosen example is a one-dimensional convection-diffusion problem with an expansion critical or turning point.